Pengaruh Lingkungan Kerja Dan Stres Kerja Terhadap Loyalitas Karyawan PT Sinar Asia Fortuna Di Rembang - Linawati Linawati; Yunaita Rahmawati (Niqosiya: Journal of Economics and Business Research, 2024)
This research aims to determine and analyze the influence of the work environment and work stress on employee loyalty at PT Sinar Asia Fortuna in Rembang, both partially and simultaneously. The type of research used is quantitative research. In collecting data, researchers used a questionnaire distributed to permanent employees. Meanwhile, the sample in this study was obtained from a purposive sampling technique. As for data processing and analyzing data, researchers used the classic assumption test method, multiple linear regression test, t-test, and F test. The study results showed that work environment significantly affects employee loyalty at PT Sinar Asia Fortuna in Rembang, and work stress significantly affects loyalty at PT Sinar Asia Fortuna in Rembang. Simultaneously, work environment and work stress have a significant effect on the loyalty of PT Sinar Asia Fortuna the goodness of fit from modeling of the work environment and work stress on employee loyalty is 44.8%, and other variables influence the rest.